Combination of Slow Deep Breathing Technique and Lavender Aromatherapy on Labor Pain Intensity Period I Active Phase in Maternity Patients Primipara at dr. Abdul Rivai Berau Hospital - Sari, Vezi Desma; Purwanti, Heni; Meihartati, Tuti; Hartati, Dwi (Institute Of Computer Science (IOCS), 2024)
Labor pain in the first stage of the active phase felt by primiparous mothers at dr. Abdul Rivai Hospital is like a strong and very scary stab, and in facing labor pain, primiparous mothers do not know how to deal with the pain they feel, so some primiparous mothers are agitated, screaming, hitting their husbands, asking for a Caesarean section without medical indication. This study aimed to determine the effect of the combination of the Slow Deep Breathing technique and lavender aromatherapy on the intensity of labor pain during the first active phase in primiparous mothers giving birth. The Study used pre-experimental methods and a group Pre-Test-Post-Test Design with a population of primiparous mothers giving birth at Dr Abdul Rivai Hospital, Berau Regency, with an average of 43 people per month, based on the Lameshow formula with a sample of 35 people. The research instrument uses the NRS scale. Data analysis used the Wilcoxon test. The score for labor pain in the first stage of the active phase before the combination of the Slow Deep Breathing technique and lavender aromatherapy carried was 8, and after the combination of the Slow Deep Breathing technique and lavender aromatherapy was 7. There is an effect of the combination of the Slow Deep Breathing technique and lavender aromatherapy on the intensity of labor pain in the active phase of the first stage in primiparous women giving birth (p-value = 0.000 < ?: 0.05). This indicates that the combination of the Slow Deep Breathing technique and lavender aromatherapy influences reduces the intensity of labor pain during the first active phase in primiparous women giving birth